2013
DOI: 10.11145/j.biomath.2013.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Identification in Population Models for Insects Using Trap Data

Abstract: BIOMATH h t t p : / / w w w. b i o m a t h f o r u m . o r g / b i o m a t h / i n d e x . p h p / b i o m a t h /Abstract-Traps are used commonly to establish the presence and population density of pest insects. Deriving estimates of population density from trap data typically requires knowledge of the properties of the trap (e.g. active area, strength of attraction) as well as some properties of the population (e.g. diffusion rate). These parameters are seldom exactly known, and also tend to vary in time, (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…It is similar in spirit to another recent model26, which was motivated by the spread of Bactrocera fruit flies in Africa. Dufourd and colleagues examine the question of trap placement optimization, an important practical question that the current study could also inform.…”
Section: Discussionsupporting
confidence: 70%
“…It is similar in spirit to another recent model26, which was motivated by the spread of Bactrocera fruit flies in Africa. Dufourd and colleagues examine the question of trap placement optimization, an important practical question that the current study could also inform.…”
Section: Discussionsupporting
confidence: 70%
“…Then, the right hand sides of (18) and (20) are the same at EE # . This implies that EE # is an equilibrium of (20).…”
Section: Theoretical Analysis Of the Control Modelmentioning
confidence: 99%
“…When γM > Y + Y P , system (17) is reduced to system(18) and it can be written asẋ= R(x) − T (x), + µ I )I (ν Y + µ Y )Y − rν I I − δF (δ + µ F )F − ν Y Y µ M M − (1 − r)ν I I…”
mentioning
confidence: 99%
“…Traps are utilized to detect and delimit small isolated insect populations and to estimate abundance and periods of activity [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Extensive research has been conducted over the years to establish the range of trap attraction, evaluate trap efficiency, estimate effective sampling area and catch probability, with the ultimate goal of interpreting trap catches and relating them to the actual population density [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Recent research by Bau and Cardé [ 26 ] demonstrated a high probability of false-negative trap catches when the density of an insect population is low and concluded that trap efficiency had a profound effect on detectability.…”
Section: Introductionmentioning
confidence: 99%